2015
DOI: 10.1002/ece3.1766
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prolonged drought on the anatomy of sun and shade needles in young Norway spruce trees

Abstract: Predicted increases in the frequency and duration of drought are expected to negatively affect tree vitality, but we know little about how water shortage will influence needle anatomy and thereby the trees’ photosynthetic and hydraulic capacity. In this study, we evaluated anatomical changes in sun and shade needles of 20‐year‐old Norway spruce trees exposed to artificial drought stress. Canopy position was found to be important for needle structure, as sun needles had significantly higher values than shade ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 42 publications
2
15
0
Order By: Relevance
“…This study follows up previous studies in the same experimental stand (see Gebauer et al 2011Gebauer et al , 2015 and we sampled needles from the same trees used in these studies. Further details about the study site and experimental design can be found in Gebauer et al (2011).…”
Section: Study Site and Experimental Designmentioning
confidence: 99%
See 3 more Smart Citations
“…This study follows up previous studies in the same experimental stand (see Gebauer et al 2011Gebauer et al , 2015 and we sampled needles from the same trees used in these studies. Further details about the study site and experimental design can be found in Gebauer et al (2011).…”
Section: Study Site and Experimental Designmentioning
confidence: 99%
“…However, very few studies have focused on the structural response of Norway spruce needles to drought, even though needles are the key organ for photosynthesis and transpiration. One of the few existing studies on Norway spruce needles found that drought reduced needle tracheid dimensions, needle cross-sectional area, and needle xylem area (Gebauer et al 2015). In another study, drought was found to increase the area of the needle vascular cylinder (Kivimäenpää et al 2003), but Gebauer et al (2015) observed negligible changes in this trait.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Within‐crown variation in water and light availability induces leaf‐level responses in conifers that reflect a combination of biophysical constraints on leaf growth and functional traits supporting both water stress tolerance and photosynthetic efficiency (Niinemets and Kull, ,; Niinemets, ; Cescatti and Zorer, ; Ishii et al., ; Ambrose et al., ; Gebauer et al., , , ). In all tall conifers studied to date, leaf length decreases while leaf mass per projected area (LMA) increases with height.…”
mentioning
confidence: 99%